Attitudes towards inclusive schooling : a study on students', teachers' and parents' attitudes - Schwab, Susanne (Waxmann, 2018)
Over the last two decades, the implementation of inclusive schooling has increased significantly in European countries and worldwide. According to empirical evidence, one of the most important success factors in implementing inclusive schooling are the attitudes of the actors involved. Previous studies have shown that positive attitudes towards inclusive schooling are not only a condition for success regarding the implementation, but also an important outcome variable of inclusive education. The present study provides empirical insights into the attitudes towards students with learning disabilities and behavioral disorders. A study called ATIS-STEP (Attitudes Towards Inclusive Schooling - Students', TEachers' and Parents' Attitudes) was conducted in the school year 2016/17 in 48 inclusive classrooms in Austria. It is the first study to provide longitudinal data that examines the attitudes of the three different stakeholder groups: students, teachers and parents. Furthermore, the interdependency of the attitudes of the three groups, as well as the influence of previous contact experience on the attitudes are analyzed and discussed.
Keywords: Inclusive education.; Educational sociology.; Mainstreaming in education.; Intégration scolaire.; Sociologie de l'éducation.; Mainstreaming in education; Educational sociology; Inclusive education